Management Strategies in English Teaching Methodologies: A Bibliometric Analysis of Communicative Language Teaching - Han-Kwang Chen (Management Analytics and Social Insights, 2024)
In the contemporary era of globalization, the significance of the English language has become paramount, necessitating a heightened focus on English education and the refinement of teaching methodologies for enhanced efficiency. This study employs the bibliometric tool VOSviewer to analyze 8,863 and 484 publications about "English Teaching Method" and "Communicative Language Teaching", respectively, spanning the past 50 years. Leveraging extensive literature data from the Scopus database, the researcher first provides a comprehensive overview of the keywords' contextual landscape. The subsequent categorization includes (1) publishing countries, (2) publishing authors, (3) publication keyword ranking, and (4) the top ten and top five cited related literature. Finally, the researcher presents conclusive findings and recommendations for future research endeavors in English Teaching Methodology. This paper contributes valuable insights into the evolving landscape of English language education, offering a foundation for further scholarly exploration.